1st International congress on pedagogical mediation in language learning - Gómez Sáenz, Cenaida; Martínez Verdugo, Diana Liceth; Linda Susan , Linda Susan; Acosta López, Juan Carlos (Memorias, 2022)
The 1st International Congress on Pedagogical Mediation in Language Learning "Facing New Challenges in the 21st Century", was held virtually on June 9th and 10th, 2022. Its main objective was to exchange research experiences in national and international contexts and to encourage the appropriation and implementation of a pedagogical mediation that responds to the challenges of the 21st century.